Advanced fractal analysis of nanoscale topography of Ag/DLC composite synthesized by RF-PECVD - Ţălu, Ştefan; Abdolghaderi, Senour; Pinto, Erveton Pinheiro; Matos, Robert Saraiva; Salerno, Marco (Surface engineering, 2020)
We present an advanced image analysis study of the 3D surfaces of silver/diamond-like carbon nanocomposite films prepared by radio-frequency plasma-enhanced chemical vapour deposition. Atomic force microscopy data were analysed, with the goal to provide image analysis tools allowing for a better understanding of the structure-property correlation, with specific case for the present material. While the samples' fractal dimension decreased and the roughness increased with increasing deposition time, fractal succolarity showed no significant difference and relatively high values, describing high percolation, and fractal lacunarity decreased, in agreement with topographic entropy, which revealed uniformity in height distribution. In conclusion, the samples' microtexture shows a nearly uniform surface with a homogenous distribution of nanoparticles, due to the fabrication process and the emerging fractal nature of the nanocomposite, at all the considered deposition times. Fractal lacunarity and succolarity, currently not provided by commercial image analysis programmes, can be useful in advanced surface image characterization.